Performance analysis of a solar photovoltaic hybrid system for electricity generation and simultaneous water disinfection of wild bacteria strains. (1st June 2016) - Pichel, N.; Vivar, M.; Fuentes, M.
Graphical abstract: Highlights: A new hybrid solar water disinfection and energy generation system was designed and tested. SOLWAT comprises a water disinfection reactor and a PV module fully integrated into a single unit. Natural water with wild strains of E. coli, Enterococcus spp. and C. perfringens were studied. The water disinfection reactor located above the PV module did not affect the final energy output. The SOLWAT disinfection results were always higher than conventional PET bottles. Abstract: A hybrid solar water disinfection and energy generation system for meeting the needs of safe drinking water and electricity was designed and tested in Alcalá de Henares (Spain) under summer climatic conditions to demonstrate the feasibility of the concept. Natural water sources with wild strains of Escherichia coli, total coliforms, Enterococcus spp. and Clostridium perfringens (including spores) were studied. Results showed that SOLWAT disinfection efficiency was higher than conventional PET bottles and that the water disinfection reactor located above the PV module did not affect the total energy output produced by the hybrid system in comparison to the single PV module, achieving the same power losses over the 6 h of sun exposure in relation to their power at standard test conditions (STC).